2013
DOI: 10.1590/s0102-05362013000100025
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização morfológica, produtividade e rendimento comercial de cultivares de alho

Abstract: OBrasil é o segundo maior consumidor e o maior importador de alho (Allium sativum) do mundo (Souza & Macêdo, 2009). Apesar da crescente oferta do produto no mercado interno, a produção brasileira é insuficiente para atender à demanda nacional (Backes et al., 2008), devido à baixa produtividade (8,2 t ha -1 ) (Souza & Macêdo, 2009). O Brasil tem condições de elevar sua produção a ponto de suprir a demanda interna e até mesmo tornar-se exportador do produto. Uma das vertentes para alcançar tal êxito é a avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 11 publications
1
20
0
2
Order By: Relevance
“…The results of total yield of cv. Amarante found in this study agree with those found by Silva et al (2000), which was 10.86 t/ha, but were well above 2.5 t/ha found by Resende et al (2013), which demonstrate the need to understand the ecophysiological aspects of the crop, as discussed below.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results of total yield of cv. Amarante found in this study agree with those found by Silva et al (2000), which was 10.86 t/ha, but were well above 2.5 t/ha found by Resende et al (2013), which demonstrate the need to understand the ecophysiological aspects of the crop, as discussed below.…”
Section: Resultssupporting
confidence: 92%
“…Despite the increasing supply of garlic in the domestic market, the Brazilian production is insufficient to meet national demand (Resende et al, 2013, Lopes et al, 2016a. Brazil is a major consumer and the world's second largest importer of garlic.…”
Section: Introductionmentioning
confidence: 99%
“…The use of virus-free garlic seeds has resulted in plants with greater vigor, mainly due to the absence of degenerations caused by viruses. Consequently, these plants have greater bulb yield than those from conventional seeds, and bulbs with better quality and good prospects for food industries, adding value to the product (RESENDE et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Resende et al (2013) found 4.1 Mg ha -1 for the Gigante-do-Nucleo and 3.1 Mg ha -1 for the BRS-Hozan, relating the high yield results to the low temperatures (13.5 to 24.5°C) and high altitude (1.025 m) of the experiment location (Guarapuava PR), which was very different from those in Barauna and Governador Dix-sept Rosado.…”
Section: Resultsmentioning
confidence: 74%